Rapid Review: I-Voting for the 2024 General Election in Indonesia - Daniel Gilrandy Tirasbudi; Irwansyah (PT FORMOSA CENDEKIA GLOBAL, 2022)
Industry 4.0 has brought technological advances in making more contributions to human life. This progress has an impact on every aspect of human life, especially information and communication technology. The Uses and Gratifications Theory (UGT) is the basis for increasing the number of participation in the general election system that meets the needs of voters. This research was conducted using a rapid review with the aim of producing policy-making recommendations to the government quickly with a limited time. The method used in the search for coherent research is PRISMA, to find media choices that are most widely used by Indonesians and find opportunities including the threat of i-voting in the 2024 simultaneous General Elections in Indonesia. The findings show the many advantages of the i-voting system because there are more benefits large compared to conventional systems, especially i-voting is an efficient system compared to previous general election systems. The main threat to the i-voting system lies in network security, this condition already has a solution, namely the blockchain. Changes in the general election system cannot be restrained because of technology, currently changes in the general election system are still stagnant due to political interests. The development of a relevant system to implement is a combination of i-voting and e-voting, this system is able to provide solutions for voters who have resource constraints with e-voting and time constraints with i-voting